IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI MADRASAH IBTIDAIYAH - Mukarromah, Azizatul; Ansori, Muhamad (International Conference on Humanity Education and Society (ICHES), 2024)
This research aims to describe the response of educators in implementing the independent learning curriculum at Madrasah Ibtidaiyah Darul Ulum Tugusari Bangsalsari Jember. The method used in the research is descriptive qualitative research. The results of the research show that the implementation of the independent learning curriculum has been responded well by Madrasah Ibtidaiyah Darul Ulum Tugusari Bangsalsari Jember. One indication is that gradually, this institution started implementing the independent learning curriculum, namely in grades 1 and 4. The implementation of the independent learning curriculum uses independent learning package books and LKS books held by students. In implementing this independent learning curriculum, this Madrasah does not yet have The RPP for the Independent Learning Curriculum is due to the fact that there is still no further training related to the Independent Curriculum in the relevant schools, but this Madrasah teacher can understand the Independent Learning Curriculum which comes from the head of the Madrasah and searches on Google, both on the form and model of the Independent Curriculum and how to implement it. Until now , the independent curriculum is implemented within a period of approximately two months from the start of the even semester and is still in a gradual system.